Analisis jenis mineral magnetik dari polutan kendaraan bermotor menggunakan metode Isothermal Remanent Magnetization (IRM) di Kota Padang (Analysis of magnetic mineral types from motorized vehicle pollutants using the Isothermal Remanent Magnetization (IRM) method in Padang City) - Pramita Syafrina; - Mahrizal; Harman Amir (PILLAR OF PHYSICS, 2013)
Polution is big problem in many city. Iron-oksida is very small and dangeraous for healty, so important to measure who give information about magnetic field. The source of polution are mount eruption, forest fire and  motor vehicle. In this eksperiment we studying about kind polution from motor vehicle. The kind polutan of vehicles was know with Isothermal Remanent Magnetization (IRM) method. In this eksperiment 93 sample, 45 top soil sample, 40 wood sample and 8 for leaf sample. The result of data analysis indication that intensity magnetization of top soil is 10.24 to 11.974.558 mA/m for wood sample is 0,22 to 7.186,20 mA/m and for leaf 0.33 to 900.31 mA/m. The analysis for saturation kurva of IRM for samples is magnetite (Fe3O4) because out field ≤ 300 mT.  Keywords: Isothermal Remanent Magnetization (IRM), magnetite